Definición de un modelo predictivo para la deserción estudiantil en educación virtual y a distancia - Acosta Contreras, Iván Acosta; Puentes, Giovanny Alberto (Escuela Colombiana de Ingeniería Julio Garavito, 2019)
University desertion is one of the most relevant and important concerns evaluated by Higher Education Institutions in Colombia. For this reason, the purpose of this document is to describe a proposed model that allows for the understanding and identification of institutional requirements regarding student dropout and also pathway all the changes that will be required of the institution in order to achieve the expected benefits and results. It also illustrates how, through digital technologies and data analysis methodologies, it is possible to identify more reliable levels of precision in order to predict possible students who may fall into student absenteeism and/or dropout. With this context, a practical approach of the proposed methodology has been carried out in a real-life scenario and in the company of a university in Colombia that has been a pioneer in the virtual education modality, where the strategic and operative understanding of the business areas that participate in the processes of information analysis for student dropout was carried out and together with this algorithms and techniques of data analysis were applied to the students allowing to obtain experimental results that achieved reliable levels of precision to identify predictions of student absenteeism and dropout. The final result is presented for discussion with the institution so that the university can define initiatives to reduce the dropout rate by identifying possible causes of student dropout.

La deserción universitaria es una de las preocupaciones más relevante e importantes que evalúan las Instituciones de Educación Superior (IES) en Colombia. Es por ello que este documento describe y propone un modelo que permite entender e identificar requerimientos institucionales acerca de la deserción estudiantil y además se mapeen todos los cambios que se les requerirán a la institución para lograr los beneficios y resultados esperados, también se ilustra como a través de tecnologías digitales y metodologías de análisis de datos se logra identificar niveles de precisión más confiable a fin de predecir posibles estudiantes que pueden caer en el ausentismo estudiantil y/o deserción estudiantil. Con esto en contexto, se ha realizado en un escenario de la vida real un enfoque practico de la metodología propuesta y en compañía de una universidad en Colombia que ha sido pionera en la modalidad de educación virtual, en donde se realizo el entendimiento estratégico y operativo de las áreas de negocio que participan en los procesos de análisis de información para la deserción estudiantil y junto con ello se aplico algoritmos y técnicas de análisis de datos a los alumnos permitiendo obtener resultados experimentales que lograron niveles confiables de precisión para identificar predicciones de ausentismo y deserción estudiantil. El resultado final se presenta a discusión con la institución a fin de que la universidad pueda definir iniciativas que permitan disminuir la tasa de abandono mediante la identificación de posibles causas de deserción estudiantil.
Keywords: Deserción estudiantil- Educación Superior- Colombia; Educación Virtual; Educación a distancia; Análisis de datos- Educación Superior; Student drop-out - Higher Education- Colombia; Virtual education; Long distance education; Data Analysis - Higher Education